Uso do óxido nítrico em pediatria - Fioretto, José Roberto [UNESP] (FapUNIFESP (SciELO), 2003)
Objective: To review the literature on inhaled nitric oxide and to describe its main clinical applications in pediatrics. Sources of data: A 10 year literature review with selection of the most important publications on inhaled nitric oxide, using the Medline and Cochrane Systematic Review databases. Summary of the findings: This review was organized as follows: introduction; metabolism and biological effects; clinical applications; dosage, gas administration and weaning; precautions and side-effects. Inhaled nitric oxide use was described in persistent pulmonary hypertension and hypoxia of the newborn, acute respiratory distress syndrome, primary pulmonary hypertension, heart surgery, chronic obstructive pulmonary disease, sickle cell anemia, and bronchospastic disease. Conclusions: Inhaled nitric oxide is a therapeutic approach with wide clinical applications in pediatrics. Its use is safe when administered in pediatric intensive care units under strict monitoring. As a pulmonary vasodilator, nitric oxide has beneficial effects on gas exchange and ventilation. Controlled trials, focusing on early gas administration should be performed under many clinical conditions, especially acute respiratory distress syndrome.
Inhaled nitric oxide in pediatrics
Keywords: Inhaled nitric oxide; Mechanical ventilation; Pediatrics; Pulmonary hypertension; corticosteroid; dobutamine; dopamine; nitric oxide; surfactant; bronchospasm; chronic obstructive lung disease; congenital heart disease; data analysis; drug effect; drug mechanism; drug metabolism; drug safety; drug screening; drug utilization; heart surgery; heart transplantation; human; inhalation; medical information; methemoglobinemia; newborn hypoxia; pulmonary hypertension; respiratory distress syndrome; review; sickle cell anemia; side effect; treatment contraindication; treatment indication; weaning; Administration, Inhalation; Child; Child, Preschool; Humans; Infant; Infant, Newborn; Intensive Care; Lung Diseases; Nitric Oxide; Vasodilator Agents